Functional and cardioprotective effects of simultaneous and individual activation of protein kinase A and Epac. (14th February 2017) - Khaliulin, Igor; Bond, Mark; James, Andrew F; Dyar, Zara; Amini, Raheleh; Johnson, Jason L; Suleiman, M‐Saadeh
Abstract : Background and Purpose: Myocardial cAMP elevation confers cardioprotection against ischaemia/reperfusion (I/R) injury. cAMP activates two independent signalling pathways, PKA and Epac. This study investigated the cardiac effects of activating PKA and/or Epac and their involvement in cardioprotection against I/R. Experimental Approach: Hearts from male rats were used either for determination of PKA and PKC activation or perfused in the Langendorff mode for either cardiomyocyte isolation or used to monitor functional activity at basal levels and after 30 min global ischaemia and 2 h reperfusion. Functional recovery and myocardial injury during reperfusion (LDH release and infarct size) were evaluated. Activation of PKA and/or Epac in perfused hearts was induced using cell permeable cAMP analogues in the presence or absence of inhibitors of PKA, Epac and PKC. H9C2 cells and cardiomyocytes were used to assess activation of Epac and effect on Ca 2+ transients. Key Results: Selective activation of either PKA or Epac was found to trigger a positive inotropic effect, which was considerably enhanced when both pathways were simultaneously activated. Only combined activation of PKA and Epac induced marked cardioprotection against I/R injury. This was accompanied by PKCε activation and repressed by inhibitors of PKA, Epac or PKC. Conclusion and Implications: Simultaneous activation of both PKA and Epac induces an additive inotropic effect and confers optimal and marked cardioprotection against I/R injury. The latter effect is mediated by PKCε activation. This work has introduced a new therapeutic approach and targets to protect the heart against cardiac insults.